Pengaruh Media Sosial Dalam Membentuk Tren Hijrah Sebagai Sarana Dakwah Keagamaan - Rosa Lini; Bashori Bashori; Martin Kustati (Journal of Da'wah, 2025)
Social media plays a crucial role in shaping the religious identity of young people and fostering the emergence of the hijrah trend as a socio-religious phenomenon in the digital era. Although numerous studies have explored the role of preachers and online da’wah content, there remains a gap in research on the comparative impact across platforms and how educational background influences students’ understanding of hijrah. This study uses an exploratory, descriptive qualitative approach, collecting primary data through observation and user interactions on social media platforms such as YouTube, TikTok, and Instagram. The results show that UIN students tend to interpret hijrah as an intellectual process closely related to the curriculum and religious-based academic activities, while private university students are more influenced by the hijrah community and emotional and social visual da’wah content. The uniqueness of this study lies in the comparative mapping of two different educational contexts and the analysis of the cross-platform impact of social media on shaping hijrah awareness. These findings confirm that the hijrah trend is not uniform, but rather shaped through the dynamic interaction of academic, social, and religious formation in the digital world.